Computer Controlled, Surface Based Instrumentation Technique for Tendon Vibration Studies - Tsang, Kenneth; deBruin, Hubert; Archambeault, Mark (CMBES Proceedings, 2008)
Although most muscle spindle investigations have used the cat model and invasive measurement techniques, several investigators have used microneurography to record from the Ia and II fibres in humans during tendon vibration. In these studies the muscle spindle primary endings are stimulated using transverse vibration of the tendon at reflex sub- threshold amplitudes. Others have used low amplitude vibration and the H-reflex to determine reflex properties during both agonist and antagonist voluntary contractions. In the past we have developed a PC based instrument that uses Labview and a linear servomotor to study tendon reflex properties by recording H-reflexes from single tendon taps or electrical stimuli to the afferent nerve. In this paper we describe a further development of this system to provide precise vibrations of the tendon up to 65 Hz with amplitudes up to 4 mm. The resultant H-wave train is extracted from background noise via phase coherent subtractive filtering. Test results from vibrating the human distal flexor carpi radialis tendon at frequencies from 10 to 65 Hz are also presented.